Інтерлейкін-2-продукуюча активність лімфоцитів у хворих на рак щитоподібної залози у процесі радіойодтерапії - Степура, Н. М.; Замотаєва, Г. А. (Clinical Endocrinology and Endocrine Surgery, 2011)
The authors present the data on a study of the effect of iodine-131 on interleukin-2-producing activity of lymphocytes in patients with thyroid cancer depending on distant metastases and the number of radioiodine therapy courses. With this purpose, 119 patients have been followed up. The group "A" comprised 49 patients with regional metastases and Group "B" – 70 patients with distant metastases. Depending on the number of radioiodine therapy courses patients were divided into six groups. The age of patients ranged from 38 to 75 years. The control group included 22 practically healthy age-matched donors. Assessment of interleukin-2-producing activity of lymphocytes was performed at the eve and in 6 days, one and 6 months after radioiodine therapy. Administration of therapeutic iodine-131 activity (from 4130 to 4730 MBq) was found to lead to a reliable decrease in the index under study. The lowest values of interleukin-2-producing activity of lymphocytes were reported in one month after radioiodine therapy in patients with regional metastases, and in case of metastases to lungs such a decrease was noted earlier (on day 6). It has also been shown that with increasing total exposure dose received by the patients in the process of repeated radioiodine therapy courses, interleukin-2-producing activity of lymphocytes was decreasing.